Hyaluronic acid as a biomaterial for dental pulp regeneration: a systematic review of preclinical studies - Al-Masoody, Azal Hadi; Hodjat, Mahshid; Kashi, Tahereh Sadat Jafarzadeh (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionWith the current advancements in regenerative medicine, it has become necessary to refine the current regenerative endodontic procedure (REP). Scaffold improvement, including the use of hyaluronic acid as a natural biomaterial, has been the subject of many studies. This systematic review aims to explore the effects of hyaluronic acid (HA) on dental pulp regeneration.MethodsA comprehensive search on Hinari, PubMed, Springer, and ScienceDirect databases in July 2024 was carried out. All in vitro and animal studies that assessed the effects of HA on cell vitality, proliferation, dentinogenesis, neovascularisation and neurogenesis in an endodontic context were included. Clinical studies were excluded. All articles were screened and assessed for relevance by the authors. The quality and risk of bias of the included studies were evaluated using the QUIN, SYRCLE, and ARRIVE Essential 10 tools.ResultsA total of 23 articles were included, comprising 17 in-vitro, 5 animal, and 1 combined in vitro and animal study. Thematic synthesis of results was adopted. The methodologies for HA addition, HA concentration and molecular weight were different across the articles. Most in-vitro studies showed that HA have a neutral effect on cell proliferation, and a positive effect on dentinogenesis and neovascularisation. Most animal studies showed increased dentine bridge formation.DiscussionThe variability in the study design has made it difficult to assert the results; however, most studies agree that HA has promising potential in REP.Systematic Review Registration[https://osf.io/t45ec/].